Green training and green supply chain management: evidence from Brazilian firms. (10th March 2016) - Teixeira, Adriano Alves; Jabbour, Charbel Jose Chiappetta; de Sousa Jabbour, Ana Beatriz Lopes; Latan, Hengky; de Oliveira, Jorge Henrique Caldeira
Abstract: The implementation of green supply chain management practices, such as green purchasing and cooperation with customers, presents several challenges, often due to a lack of green training. In order to analyze the relationship between green training and green supply chains, a survey of Brazilian firms with ISO 14001 certification was conducted. The main characteristics of green training in the sample were also explored. The results indicated that green training is positively correlated with the adoption of green supply chain practices in green purchasing and cooperation with customers, confirming the study's main hypothesis. The research results also indicated that green training tends to help firms improve their green supply chain management to cooperate with customers and implement green purchasing. This work extends the current literature by showing that employees' green training content and requirements for greening suppliers should be further aligned. This alignment should also involve cleaner production priorities built up through customer cooperation. As a consequence, firms will reach internal environmental targets and achieve external environmental improvements (such as through having greener suppliers). Finally, we also discovered the main characteristics of green training that can galvanize green supply chain management, including the following: green training topics that are appropriate and current for company activities, green training contents created through a systematic analysis of training gaps and needs; and employees who receive green training and have the opportunity to apply green knowledge in everyday activities. Highlights: This work analyzed the relationship between GSCM (green purchasing and collaboration with customers) and green training. We presented empirical evidence from Brazilian firms. This research showed that green training is positively related to GSCM. We highlighted the necessary alignment of green initiatives, customers, suppliers and anchor firms in a supply chain.